Physicochemical properties and consumer preference of imitation chicken nuggets produced from chickpea flour and textured vegetable protein - Sharima-Abdullah, N; Hassan, CZ; Arifin, N; Huda-Faujan, N. (Univ Putra Malaysia Press, 2024)
In recent years, consumers' demand increases for healthier foods with nutritional benefits and similar taste to the origin. Thus, this study was conducted to evaluate the physicochemical properties and proximate composition as well as consumer preference of imitation chicken nuggets or ICNs formulated with different percentage of chickpea flour and textured vegetable protein (TVP). A commercial brand of chicken nugget was chosen as control experiment to compare its characteristics with ICNs. Five formulation of ICNs were prepared with the percentage of chickpea flour to TVP of ICNs were: A (30: 10), B (25: 15), C (20: 20), D (15: 25), and E (10: 30). Results found that all ICNs were found significantly lower (P< 0.05) in cooking loss, lightness, hardness, chewiness, springiness, cohesiveness, and water activity than in control nugget. However, all ICNs were higher (P< 0.05) in yellow colour than in control nugget. The ash, protein, and carbohydrate contents of ICNs were higher (P< 0.05) than in control nugget but were lower (P< 0.05) in moisture and fat content. However, hedonic test found that consumers preferred (P< 0.05) control nugget compared to all ICNs. The ICN E which contained percentage of chickpea flour to TVP (10: 30) was the most preferred by consumers in term of texture, taste, and overall acceptance compared to all ICNs. This findings showed that formulation of ICNs with chickpea flour with TVP could be accepted by consumers but further research should be focused on the optimised amounts of the chickpea flour in the ICNs. Thus, the sensory characteristics with these proteins and the nutritional values should be improved similar to those with chicken. (c) All Rights Reserved